Comparison of Action Marks on Cartridge Cases Discharged from 9mm Walther P99 Models AS and QA Semiautomatic Pistols on Repeated Firing - Azahidi, Azahiri (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
A fireann identification expert sometimes find it difficult to draw conclusions when comparing fired ammunitions found at the crime scene with the firearm that is recovered after some time interval. During the period, the firearm might have been subjected to any changes due to prolonged repeated firing. This project work investigated any changes and alterations of the action marks recorded on the expended cartridge cases due to repeated firing of 9mm Walther P99 semiautomatic pistols models Anti Stress (AS) (RMP 10248, RMP 10263) and Quick Action (QA) (RMP 61077, RMP 61089, RMP 61100). Each pistol had been repeatedly fired for at least 740 rounds, on the occasion of the shooting practice for police officers of Kelantan State. Cartridge cases of every consecutive of 40th rounds were recovered. Examination using Leica Forensic Solution Comparison (FS C) microscope under magnification x 10 to x60 was conducted to observe class and individual characteristics produced by each pistol. Class characteristics of AS and QA models showed many similarities, since they are the variants of the same family of Walther P99. Positive identification between the last cartridge case with the first cartridge case could be made based on breech face marks, firing pin impressions, extractor marks and striation marks that were found on the rim. The study had shown that prolonged repeated firing of guns may cause some changes of action marks but the changes are not significant, hence identification could be made.